(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article presents the practical application of the methodology Circular Planning for Fiber and Notion Compatibility, previously developed as a strategy to mitigate the so-called hybrid monsters in sustainable fashion upcycling projects. The research was carried out with the women’s collective Instituto Criar Mulher, through the Eco-Criativas workshop, which used bus driver uniforms as raw material for textile experimentation and reconversion. Grounded in Freirean principles of popular education, the extension activity proposed a dialogue between technical knowledge and life experience, fostering collective learning, autonomy, and women’s protagonism. The methodology was applied in five stages: material diagnosis, compatibility mapping, creative exploration, process documentation, and educational communication. The process resulted in the creation of prototypes that combine circularity, aesthetics, and environmental awareness. The results indicate that the integration of design, extension, and dialogical pedagogy strengthens fashion as a field of social and environmental transformation, consolidating upcycling as an instrument of emancipation and citizenship.